Readiness of Albanian Students to engage in Digital Learning: Perceptions, Challenges and Opportunities (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Digital technologies play a crucial role in transforming today’s learning landscape. The integration of online platforms, digital learning materials, and collaborative tools has become commonplace in many countries, offering students access to various resources and opportunities for engagement both inside and outside the classroom. This shift towards digital learning fosters a more dynamic and motivating learning environment and equips students with employability skills, enhancing their prospects in today's labour market. Recognizing the significance of digitalization in education, Albania has prioritized this initiative as part of its efforts to align with EU standards. Despite ongoing projects and investments aimed at promoting digitalization of teaching and learning, the pace of adopting innovative approaches remains sluggish, largely due to the complex interplay of factors and the readiness of key stakeholders such as teachers, school leaders, and students. To explore the challenges and identify potential solutions, a research study was conducted among students at the University of Tirana. By combining survey data with in-depth interviews, the research aims to uncover students' perceptions toward digital learning. The research shows that Albanian students are aware on the importance of digital learning, but are still facing psychological and infrastructural challenges that hinder their perceived readiness and willingness.